Shaping consumer intention in emerging markets: the role of personality traits in foreign product preference - Ariffin, Nurul Azrin; Mohd Daud, Norzaidi; Jamaludin, Nor Lelawati (Faculty of Business and Management, 2025)
This study examines what drives consumers in an emerging market to choose foreign hygiene products, using the Theory of Planned Behaviour (TPB) as its foundation. It focuses on two key influences, social norms and perceived behavioural control and explores whether personality traits play a mediating role in shaping purchase intention. Data were gathered from 260 Malaysian consumers through a structured survey and analysed using partial least squares structural equation modelling (PLS-SEM). The findings show that both social norms and perceived control significantly affect purchase intention. Perceived control also shapes personality traits, which themselves influence intention, though personality traits do not mediate the overall relationships. By extending TPB with personality factors, this study sheds light on consumer decisionmaking in the context of foreign products, an area often overlooked in emerging market research. From a business perspective, the results suggest that companies should focus on strengthening consumers’ sense of control and responding to social influence rather than relying on personality-based segmentation. These insights are valuable for multinational firms and local entrepreneurs aiming to refine product positioning and build stronger connections with consumers in globalised markets.